Shaft Twist Moment Analysis of Turbocharger ABB Type VTR 354 Due to Surging Phenomenon - Beny Cahyono; Aguk Zuhdi Muhammad Fathallah; Istiqomah Istiqomah; Semin Semin (Institut Teknologi Sepuluh Nopember, 2019)
Surging is a phenomenon in which the airflow back toward of the compressor side. This case is known by excessive sound or vibration in the turbocharger. The main cause of surging phenomenon is divided into two types, that is failure operation by crew and improper selection turbocharger by the designer. This research identifies the effect of surging on twisting moment of turbocharger shaft ABB type VTR 354 on Niigata 8MG40X engine. The method is using simulation based on Finite Element Method (FEM), start from determining the compressor and turbine torque then preparing the turbocharger shaft and simulation with SolidWorks. It is found that critical area caused by surging is located on compressor seat. The largest torque difference at 50% of the engine load about -1.304 Nm and maximum stress is about 0.015906 Mpa, while the displacement is about 0.0000270028 mm and the maximum strain is about 6.26693e-008 mm/mm. Thus, the shaft material 17NiCrMo6-4 is considered capable of dealing with surging on the turbocharger.